Investigating the nonlinear behavior of Eccentrically Braced Frame with vertical shear links (V-EBF). (March 2017) - Vetr, Mohamad Ghasem; Ghamari, Ali; Bouwkamp, Jack
Abstract: The excellent hysteretic behavior of Eccentrically Braced Frames (EBFs) using shear links have made these systems an effective alternative for both moment resisting frame as well as concentrically braced structures. In common practical horizontal shear links are located either at the middle or at the ends of the beam section. However, large deformation of the shear links in those beam must be accepted under severe earthquakes. In those instance in which the beam has to remain elastic, vertical shear links should be designed underneath the beam thereby transferring the region of plastic deformation to location where they are tolerable and post-earthquake repair or replacement of damaged parts is easier. In this paper, seismic behavior of Vertical-EBF (V-EBF) have been considered experimentally and analytically. The required relation to design of the system have been proposed. Also, to predict nonlinear behavior of V-EBF systems, an analytical model including Kinematic-Isotropic strain hardening for shear, only kinematic strain hardening for moment, has been presented. Results showed a good convergence of the presented analytical model (with an upper bound for yielding surface to the V-EBF) with experimental results. Highlights: The three story test model have been added. The relations have been suggested to design of V-EBF. An simple model has been proposed to nonlinear analysis of V-EBF.